Community-based models of care facilitating the recovery of people living with persistent and complex mental health needs: a systematic review and narrative synthesis - Harvey, Carol; Zirnsak, Tessa-May; Brasier, Catherine; Ennals, Priscilla; Fletcher, Justine; Hamilton, Bridget; Killaspy, Helen; McKenzie, Peter; Kennedy, Hamilton; Brophy, Lisa (Frontiers in Psychiatry, 2023)
Objective This study aims to assess the effectiveness of community-based models of care (MoCs) supporting the recovery of individuals who experience persistent and complex mental health needs. Method We conducted a systematic review and narrative synthesis of MoC studies reporting clinical, functional, or personal recovery from October 2016 to October 2021. Sources were Medline, EMBASE, PsycInfo, CINAHL, and Cochrane databases. Studies were grouped according to MoC features. The narrative synthesis was led by our researchers with lived experience. Results Beneficial MoCs ranged from well-established to novel and updated models and those explicitly addressing recovery goals and incorporating peer support: goal-focused; integrated community treatment; intensive case management; partners in recovery care coordination; rehabilitation and recovery-focused; social and community connection-focused; supported accommodation; and vocational support. None of our diverse group of MoCs supporting recovery warranted a rating of best practice. Established MoCs, such as intensive case management, are promising practices regarding clinical and functional recovery, with potential for enhancements to support personal recovery. Emerging practice models that support personal and functional recovery are those where consumer goals and priorities are central. Conclusion Evidence for established models of care shows that there is a need for inevitable evolution and adaptation. Considering the high importance of effective MoCs for people experiencing persistent and complex mental health needs, further attention to service innovation and research is required. Greater emphasis on the inclusion of lived and living experience in the design, delivery, implementation, and research of MoCs is needed, to enhance MOCs' relevance for achieving individual consumer recovery outcomes.